Association of Urinary Tract Infection with Preeclampsia during Pregnancy - Fatima, Wajeeha; Shabana, Nargis; Tabasam , Shakra; Malik, Iqra Kanwal; Hanif, Aleena; Nadar , Ayesha (Indus Journal of Bioscience Research, 2025)
Background: Urinary tract infections (UTIs) during pregnancy have a wide range of impacts on fetomaternal outcomes. Objective: To find association of UTIs with preeclampsia in pregnancy. Study design: Cohort study. Place and duration of study: Obstetrics and Gynecology Department, PAF Hospital, Islamabad. Materials and Methods: After obtaining approval from Institutional Ethical Committee, 140 women coming for routine antenatal checkup were divided into two groups (exposed or non-exposed) based on having UTI. The women were followed up to parturition and frequency of preeclampsia was noted down. The data was analysed by SPSS version 25. The relative risk (RR) was calculated for the exposed and non-exposed groups. Results: The mean age of the patients was 29.91 ± 5.98 years. The mean gestational age and BMI at time of recruitment were 28.92 ± 4.37 weeks and 24.08 ± 2.58 kg/m2 respectively. Out of 140 patients, 39 (27.9%) developed preeclampsia. In the exposed group, 26 (37.1%) while in the unexposed group, 13 (18.6%) patient developed preeclampsia (p = 0.014). The RR was 2.00 (95% CI 1.123-3.563). The Odds ratio for UTI (exposed/unexposed) was 2.591 (95% CI 1.196-5.614). The binary logistic regression analysis showed that effect of confounder was not statistically significant (p = 0.077). Conclusion: UTIs independently increases preeclampsia risk in pregnancies beyond 20 weeks. Despite confounding variables, this association necessitate for routine UTI screening and early antibiotic treatment in antenatal care.